Augmented Reality (AR) Application Framework for Mathematics - Nur Izza Nabila, Ahmad (Universiti Malaysia Sarawak, 2022)
Augmented Reality has shown potential in improving the learning process for the education field. Various application has been developed for different subjects and training. Multiple AR applications have been developed for mathematics. However, there is no guideline on how to develop an effective AR application for a specific mathematics topic and how to design User Interface (UI) to assist students in gaining a better understanding of mathematics. Therefore, this study proposes an AR application framework for a specific mathematics topic. The framework components were validated using the Fuzzy Delphi Method (FDM). Using the framework, an AR application was developed, with a focus on the user interface and multimedia elements that can improve students' understanding of mathematics. The study's findings show that there is a significant difference in mean between pre-test (9.70) and post-test (11.70). Participants also gave positive feedback on the AR application's user interface. The AR application has a percentage usability score of 72.63. This suggests that the developed AR application has the potential to improve students' mathematics performance. The UI also has the potential to help students to better understand mathematics topics.